Heavy metals analysis in commercial apple drinks by inductively coupled plasma optical emission spectrometry (LCP-OES) / Nurul Nadia Mohamad Maki - Mohamad Maki, Nurul Nadia (Faculty of Applied Sciences, 2017)
Heavy metals (Cu, Pb, Ni, Cr and Cd) concentration in seven brands of apple drinks, commercialized in Malaysia were determined using inductively coupled plasma optical emission spectrometry (ICP-OES). The apple drink samples were diluted with nitric acid before being analyzed by ICP-OES. The average contents of heavy metals in apple drink samples were found from 0.003 to 0.10 mg/L for Cu, and from 0.023 to 0.06 mg/L for Pb. Cd, Cr and Ni have lower concentration than the detection limit. Hence, all these metals cannot be detected in the all apple drinks. All these elements have below permissible limit of heavy metals allowed by the Malaysian Food Regulation 1985. All of the tested apple drinks are safe to consume. Determination of major elements such as Ca, Na, Mg and K in apples drinks will be carried out in future study.